2008
DOI: 10.1007/s12206-008-0425-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution of radiative transfer within a cubic enclosure filled with nongray gases using the WSGGM

Abstract: Using a weighted sum of gray gases model with gray gas regrouping technique (WSGGM-RG), problems of radiative transfer within three-dimensional enclosures filled with non-homogeneous and non-isothermal combustion gas mixtures were solved. The radiative transfer equation was solved based on discrete ordinate method (DOM) and raytracing method (RTM) with WSGGM-RG. The results using WSGGM-RG were compared with those using the statistical narrow band (SNB) model. The average radiative intensities and radiative hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The average and maximal relative errors generally decreased with the increase in the number of regrouped gray gases, and when the number of gray gases was bigger than five, the reduction of the average and maximal relative errors became unimportant. Results presented by Coelho [10] and Park and Kim [12] showed that the difference in radiative heat transfer calculations in 3-D enclosures with fixed temperature and concentration distributions decreased with increases in the number of gray gases.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The average and maximal relative errors generally decreased with the increase in the number of regrouped gray gases, and when the number of gray gases was bigger than five, the reduction of the average and maximal relative errors became unimportant. Results presented by Coelho [10] and Park and Kim [12] showed that the difference in radiative heat transfer calculations in 3-D enclosures with fixed temperature and concentration distributions decreased with increases in the number of gray gases.…”
Section: Introductionmentioning
confidence: 95%
“…With some exceptions, an increase in the number of gray gases from 3 to 20 decreased the average and maximal relative errors. Park and Kim [12] used the regrouping technique to investigate the possibility of reducing the number of gray gases of the narrow band based WSGM. The exact values of the wall fluxes and average intensity of radiation inside the cubic 3-D enclosure with fixed temperature and concentration spatial distribution were found using the statistical narrow band model.…”
Section: Introductionmentioning
confidence: 99%